The color purple - Walker, Alice (Guild Publishing, 1986)
This book is about Celie, a young African American girl who is repeatedly raped by her father and gives birth to two children, both of whom are taken away from her. The story is told through a series of letters, initially addressed to God, as Celie has no one else to confide in. She is married off to a man she refers to as 'Mr.___', who is abusive and treats her as a servant. Throughout the novel, Celie's life is marked by hardship and suffering. She is separated from her beloved sister, Nettie, and is forced to endure the harsh realities of being a black woman in the American South during the early 20th century. Despite her circumstances, Celie remains resilient, finding solace in her relationship with another woman, Shug Avery, who becomes her confidante and lover.